Case Series of Fraser Syndrome - Desai, Purvi; Kathrotiya, Kalpana; Mehta, Dipti; Patel, Shimolee; Chauhan, Binodini (Journal of Fetal Medicine, 2025)
Fraser syndrome is an autosomal recessive multiple malformation syndrome. It has a recurrence risk of 25% among siblings; therefore, prenatal diagnosis is important for counseling of affected families. We describe three prenatal cases of Fraser syndrome. Based on new diagnostic criteria, three major, two major, and two minor criteria or one major and three minor criteria are needed for diagnosis of Fraser syndrome. It includes six “major” manifestations, including syndactyly, cryptophthalmos spectrum, ambiguous genitalia, urinary tract abnormalities, laryngeal and tracheal anomalies, and positive family history with five “minor” defects, including anorectal defects, dysplastic ears, skull ossification defects, umbilical defects, and nasal anomalies. In all three of our cases, congenital high airway obstruction syndrome (CHAOS) was a constant finding. Renal system anomalies, including renal agenesis and dysplastic kidneys, anhydramnios, and ascites, were also found in all three cases. Prenatal diagnosis of Fraser syndrome was confirmed genetically postnatally in two out of the three patients, with an excellent correlation of antenatal sonographic findings with postnatal features of the abortus. Certain anomalies like syndactyly and cryptophthalmos, which were not possible to detect antenatally because of anhydramnios, were confirmed postnatally. We conclude that cases with antenatal diagnosis of CHAOS and bilateral renal agenesis/dysplastic kidneys must be advised for meticulous postnatal examination for the remaining features of Fraser syndrome, especially ambiguous genitalia, cryptophthalmos, and syndactyly and then confirm genetically to ensure appropriate counseling of the couple for future pregnancy.
Keywords: ambiguous genitalia; bilateral renal agenesis; CHAOS; Fraser syndrome; syndactyly; upper airway malformations; cryptophthalmos spectrum